Polychromatic, sexual dimorphism and redescription species of red devil Amphilophus Amarillo [Stauffer & McKaye, 2002] in Sermo Reservoir, Yogyakarta - Sitty Ainsyah Habibie; Djumanto Djumanto; Murwantoko Murwantoko (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2018)
Red devil has been extensively researched due to extremely high morphometric and chromatophore variations, including the phenomena of polychromatic and trophic polymorphism. The purpose of this study was to identify and observe the phenomenon of sex dimorphism that occurs in polychromatic red devil species which caught in Sermo Reservoir. Fish sample as much as 240 individual was collected from fishermen catch during November 2016-September 2017 by using gill nets, cest nets, and fishing rods. Subsequently, the fish sample was grouped based on color and sex, the namely group of red devil red, red devil black, and red devil reddish black. The morphometric character data of 21 units were measured in each fish sample, whereas the DNA samples were taken from the gill tissue on each species of two individuals. The morphometric character data was analyzed for discriminant distance, while DNA was analyzed by BLAST (Basic Local Allignment Search Tools) from NCBI. The result of the principal component analysis and discriminant function showed the three group of fish can be distinguished by the characters around the head. The T-test of male and female morphometric characters in each fish group showed the phenomenon of sex dimorphism. Canonical and dendrogram diagrams consistently classify the three group of fish as the same species but are segregated by sex so that significantly dimorphism occurs. The mitochondrial sequencing results of the DNA control region show that among the red devil fish group found in the Sermo Reservoir is a species of A. amarillo. Abstrak Red devil telah banyak diteliti karena variasi morfometrik dan kromatofora yang sangat tinggi, termasuk di dalamnya fenomena polikromatisme dan trofik polimorfisme. Penelitian ini bertujuan untuk mengamati polikromatik dan dimor-fisme seksual serta mengidentifikasi spesies red devil di perairan Waduk Sermo Yogyakarta. Contoh ikan sebanyak 240 ekor diambil dari hasil tangkapan nelayan selama bulan November 2016-September 2017 dengan menggunakan jaring insang, jala dan pancing. Selanjutnya contoh ikan dikelompokkan berdasarkan warna dan jenis kelamin, yaitu kelompok red devil merah, red devil hitam, dan red devil merah kehitaman. Data karakter morfometrik sebanyak 21 unit diukur pada setiap contoh ikan, sedangkan contoh DNA diambil dari jaringan insang pada masing-masing kelompok ikan seba-nyak dua ekor. Data karakter morfometrik dianalisis pembedanya, sedangkan DNA dianalisis dengan BLAST (Basic Local Allignment Search Tools) dari NCBI. Hasil analisis komponen utama dan fungsi diskriminan menunjukkan ketiga kelompok ikan dapat dibedakan berdasarkan karakter yang berada di sekitar kepala. Uji t terhadap karakter morfome-trik jantan dan betina pada masing-masing kelompok ikan menunjukkan fenomena dimorfisme seksual. Diagram kanonikal dan dendrogram konsisten mengelompokkan ketiga kelompok ikan tersebut sebagai spesies yang sama, namun terpisah berdasarkan jenis kelamin sehingga sangat nyata terjadi dimorfisme. Hasil sekuensing mitokondria DNA control region menunjukkan seluruh kelompok ikan red devil yang ditemukan di Waduk Sermo merupakan spesies Amphilophus amarillo.